2006
DOI: 10.1182/blood-2006-03-010181
|View full text |Cite
|
Sign up to set email alerts
|

Safe and efficient transduction of the liver after peripheral vein infusion of self-complementary AAV vector results in stable therapeutic expression of human FIX in nonhuman primates

Abstract: The safety and efficacy of peripheral venous administration of a self-complementary adeno-associated viral vector encoding the human FIX gene (scAAV-LP1-hFIXco) was evaluated in nonhuman primates for gene therapy of hemophilia B. Peripheral vein infusion of 1 ؋ 10 12 vg/kg scAAV-LP1-hFIXco pseudotyped with serotype 8 capsid, in 3 macaques, resulted in stable therapeutic expression (more than 9 months) of human FIX (hFIX) at levels (1.1 ؎ 0.5 g/mL, or 22% of normal) that were comparable to those achieved after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
229
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(237 citation statements)
references
References 21 publications
7
229
1
Order By: Relevance
“…The second-generation optimized CsCl purification method described and characterized herein enables flexible purification of vectors of varying serotypes, and importantly results in consistently high vector purity and potency, and comparable in these attributes to vectors prepared for clinical studies. The use of such improved AAV purification methods for pre-clinical studies, combined with further improvements in expression cassettes, use of self-complementary AAV constructs, 23 more efficient serotypes, 8,24 and improved delivery techniques are important strategies to meet the need for high levels of therapeutic transgene expression and support successful translational research.…”
Section: Discussionmentioning
confidence: 99%
“…The second-generation optimized CsCl purification method described and characterized herein enables flexible purification of vectors of varying serotypes, and importantly results in consistently high vector purity and potency, and comparable in these attributes to vectors prepared for clinical studies. The use of such improved AAV purification methods for pre-clinical studies, combined with further improvements in expression cassettes, use of self-complementary AAV constructs, 23 more efficient serotypes, 8,24 and improved delivery techniques are important strategies to meet the need for high levels of therapeutic transgene expression and support successful translational research.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies in animals and humans have suggested that the AAV capsid mounts a very strong TD immune response. The evidence includes the following: (i) no NAb was detected after muscular injection, and AAV vector transgene expression was observed following readministration of AAV2 vector via muscular injection in MHC class II-deficient mice (42); (ii) transient immunosuppression with CD4 antibody treatment at the time of primary infection elicited no NAbs and allowed transgene expression in wild-type mice following readministration of AAV vectors (19,42,66); (iii) our prior work has demonstrated that a high NAb titer was achieved after immunization with AAV-pulsed dendritic cells in mice (34); (iv) IgG subclasses were produced in mice and primates with AAV administration (19,52,53,69); and (v) IgG subclasses were observed in humans and in patients following AAV vector treatment (6,51,54). In this study, isotype assays suggested that IgG2a is the predominant IgG subclass in all mice immunized with AAV1 to -5, which is consistent with other viruses that also elicit markedly increased IgG2a production in mice (20).…”
Section: Discussionmentioning
confidence: 99%
“…The same was shown in non-human primates using AAV5. 74 Intravenous administration of a self-complementary AAV5 vector encoding the human F.IX gene resulted in comparable levels of circulating F.IX in macaques with or without pre-existing immunity to AAV8. This confirms that alternative serotypes can circumvent pre-existing naturally acquired immunity to AAV in the non-human primate model.…”
Section: Aav Capsid Antibodies: a Persistent Challengementioning
confidence: 99%